Review of Luneburg Lens Antenna Designs Manufactured Using 3D Printing - D. V. Kusaykin; I. V. Grigoriev; D. V. Denisov; P. A. Turalchuk (Известия высших учебных заведений России: Радиоэлектроника)
Introduction. The interest in multibeam dielectric lens antenna arrays has been growing in recent years due to the development of millimeter-wave telecommunication and radar systems. Progress in the development of mobile communication systems based on adaptive beamforming technology is increasingly associated with multibeam systems based on lens antenna structures, providing an alternative to hard-to-implement and energy-consuming phased antenna arrays. In recent years, spherical and cylindrical Luneburg lens antennas implemented using additive manufacturing technology have attracted research attention. Despite their complexity of execution, these design exhibit excellent electromagnetic characteristics. This paper provides a review of Luneburg lens antennas manufactured using 3D printing, which can find application in 5G and 6G communication systems.Aim. To review achievements in the design of lens antenna structures manufactured using additive manufacturing.Materials and methods. Materials for analysis, comparison, and systematization were derived from various sources, including research articles, publications in proceedings of Russian and international conferences, and websites of manufacturers of lens antennas over the past 20 years. The material selection mechanism was based on the originality of the presented designs of printed Luneburg lens antennas.Results. A review of Luneburg lens antennas manufactured using 3D printing, which differ from each other in terms of mechanical strength, complexity of execution, and electrodynamic characteristics, was carried out. The results of a comparative analysis of the key characteristics of these antennas are presented, along with examples of their practical implementation.Conclusion. The disadvantage of Luneburg lens antennas has always been the complexity of their manufacture; however, additive manufacturing technologies open up new opportunities for their fast, high-quality, and automated production. Various 3D printing technologies can be used to create dielectric lens antennas, which differ in the resolution of printers, printing speed, and cost. Additive manufacturing methods are constantly developing, having reached the technological possibility of printing Luneburg lens for the sub-THz range with a high level of resolution and accuracy. In addition, 3D printers capable of printing multiple lenses simultaneously have also appeared.